(untitled) (Teaching and Learning Inquiry, 2022)
Engaging students in an international online setting that is interdisciplinary and culturally diverse is a challenge. A joint classroom between German and Ugandan universities used a formative assessment approach paired with active learning elements to foster individual and peer learning in an international virtual setting. A survey at three different times across the semester explored students’ perceptions towards the value of the active learning activities and evaluated how perceptions changed over time. Overall, students enjoyed the diverse active learning activities and perceived value toward their success in class. This was more pronounced and unidirectional for individual tasks than it was for group work. In addition to the findings of the structured survey, observation and feedback indicated that other elements contributed to effective course delivery. These included clear and frequent communication to the students from the primary instructor, prompt feedback from the instructor on graded exercises, such as a reflective learning diary and ungraded quizzes, and student confidence that sincere effort would achieve a good grade.